Analisis Fonologi Bahasa Kedayan - Nabilah Syazwani, Norasman (Universiti Malaysia Sarawak (UNIMAS), 2017)
The Kedayan language is spoken in Brunei, Sabah, Sarawak, and Federal Territory of Labuan. This language is considered a minority language in Sabah and Sarawak. This study is a phonological analysis of Kedayan language. The study was conducted in Bekenu, Miri in Sarawak. It involves one key informant and three main informants. The objectives of this study are, to identify the vocal and consonant system of Kedayan language; to identify phonemes, allophones, the distribution of the sound, and the functional load Kedayan language; and to identify the diphthongs, vowel clusters and consonant clusters in Kedayan language. Based on the data gathered, there are three vocal phonemes, /i, a, u/ and 18 consonant phonemes, /p, b, t, d, k, ɡ, Ɂ, m, n, ɲ, ŋ, ʧ, ʤ, s, h, l, w, j/; and nine vocal allophones